The “Sheep Rush” phenomenon and the level of social trust during the financial crisis 2008+, the COVID-19 pandemic and chosen armed attacks in the 21st century - Złoty, Marcin (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Economic and pandemic crises, along with military actions, constitute a strong cause-and-effect link between the occurrence of society’s loss of trust in the market environment in the 21st century. The occurrence of unfavourable situations is often related to the “Sheep Rush” phenomenon. The lack of regulations and effective tools to prevent and counteract market turmoil increases the mood of anxiety. Many consumers and investors, in a situation of ignorance and chaos, begin to imitate emerging market trends. In times of crisis, many citizens begin to buy gold, which increases in value with high demand, highlighting the scale of the unfavourable situation. The gold market responds to social unrest related to various types of crises. In this case, the appreciation of gold is sudden and the price trend is not short-term. The occurrence of a negative price on the crude oil futures market during the COVID-19 epidemic in May 2020 or the exceeding of the maximum historical limit of $2,100/ounce of gold in December 2023 illustrates the extremes of herd behaviour, which is based on panic. In turn, the inappropriate monetary policy of the United States based on a low interest rate in 2006 caused a global financial meltdown and continues to exert strong inflationary pressure on the property market around the world, including in Poland. The description of macroeconomic events in the 21st century well illustrates how important it is for market entities to trust each other and the market, as well as to make reasonable decisions. Otherwise, we usually deal with a market collapse and a domino effect. The sheep rush process is vital from the point of view of social and economic inequalities due to the impact of such behaviour on the prices of analysed goods and the level of international trust.

Kryzysy gospodarcze i pandemiczne wraz z działaniami militarnymi stanowią silne powiązanie przyczynowo-skutkowe występowania utraty zaufania społeczeństwa do otoczenia rynkowego w XXI wieku. Występowanie niekorzystnych sytuacji związane jest często ze zjawiskiem owczego pędu. Brak regulacji i efektywnych narzędzi do zapobiegania i przeciwdziałania zachodzącym zawirowaniom rynkowym wzmaga nastroje niepokoju. Duża część konsumentów i inwestorów w sytuacji niewiedzy i chaosu zaczyna naśladować tworzące się tendencje rynkowe. W sytuacji kryzysów duża część obywateli zaczyna nabywać złoto, które z dużym popytem zyskuje na wartości ukazując skalę niekorzystnej sytuacji. Z kolei działania militarne wiążą się z nagłą aprecjacją ceny nie tylko złota lecz i ropy naftowej. Wystąpienie na rynku kontraktów terminowych ropy naftowej ujemnej ceny w trakcie epidemii COVID-19 w maju 2020 roku czy przekroczenie maksymalnej historycznej granicy 2100 USD za uncję złota w grudniu 2023 roku pokazuje ekstrema zachowań stadnych, których fundamentem jest panika. Z kolei niewłaściwa polityka pieniężna Stanów Zjednoczonych oparta na niskiej stopie procentowej w 2006 roku wywołała światowy krach finansowy i stanowi ciągle silną presję inflacyjną na rynku nieruchomości na całym świecie, także w Polsce. Opis makroekonomicznych zdarzeń w XXI wieku dobrze ilustruje jak ważne jest zaufanie podmiotów rynkowych do siebie i rynku oraz rozsądkowe podejmowanie decyzji. W przeciwnym wypadku mamy do czynienia zazwyczaj z załamaniem rynku i efektem domino. Analizowany proces owczego pędu jest ważny z punktu widzenia nierówności społecznych i gospodarczych w kontekście wpływu takich zachowań na ceny badanych towarów i poziom zaufania między jednostkami.
Zjawisko owczego pędu a poziom zaufania społecznego podczas kryzysu finansowego, pandemii COVID-19 i wybranych działań militarnych w XXI wieku
Keywords: financial crisis; gold; epidemic; sheep rush; social trust; kryzys finansowy; epidemia; owczy pęd; złoto; zaufanie społeczne